When three's a crowd: How relational structure and social history shape organizational codes in triads - Özgecan Koçak; Massimo Warglien (Journal of Organization Design, 2020)
When members of an organization share communication codes, coordination across subunits is easier. But if groups interact separately, they will each develop a specialized code. This paper asks: Can organizations shape how people interact in order to create shared communication codes? What kinds of design interventions in communication structures and systems are useful? In laboratory experiments on triads composed of dyads that solve distributed coordination problems, we examine the effect of three factors: transparency of communication (versus privacy), role differentiation, and the subjects' social history. We find that these factors impact the harmonization of dyadic codes into triadic codes, shaping the likelihood that groups develop group-level codes, converge on a single group-level code, and compress the group-level code into a single word. Groups with transparent communication develop more effective codes, while acyclic triads composed of strangers are more likely to use multiple dyadic codes, which are less efficient than group-level codes. Groups of strangers put into acyclic configurations appear to have more difficulty establishing "ground rules" - that is, the "behavioral common ground" necessary to navigate acyclic structures. These coordination problems are transient - groups of different structures end up with the same average communication performance if given sufficient time. However, lasting differences in the code that is generated remain.
Keywords: 650; Communication codes; Code convergence; Organizational structure; Conceptual pacts; Common ground; Coordination games; Experiment; Triads; Acyclicity; Transitivity; Hierarchy; Language